Antithymocyte globulin in pediatric allogeneic hematopoietic stem cell transplantation: Infusion time and tolerability. (20th March 2020) - Sevrin, François; Gonzales, Fanny; Machuron, François; de Berranger, Eva; Bruno, Benedicte
Abstract: Antithymocyte globulin is a major drug in transplantation. rATG has been successfully used to prevent graft‐versus‐host disease in allogeneic HSCT. However, its first infusion is associated with reactions ranging from simple fevers to distributive shocks and may interfere with the transplant conditioning. To evaluate the impact of rATG infusion rate on clinical tolerability, we conducted a retrospective study of all pediatric allogeneic HSCT patients who received rATG (Thymoglobulin®) as part of their conditioning at Lille University Hospital from 2003 to 2018. Until 2012, patients received rATG with a theoretical infusion time of 12 hours (12H group, n = 33). From 2012, they had a theoretical infusion time of 4 hours (4H group, n = 43). Patients from the 12H arm presented more ≥ grade 3 infusion‐related reactions at first dose (70% versus 44%, P  = .027), had significantly higher fever (median of 39.6°C versus 39.2°C, P  = .002), and needed a greater use of symptomatic treatments. However, they received a slightly higher first dose of rATG (median of 2.7 versus 2.3 mg/kg, P  = .042). In view of these results, a rATG infusion time of 4 hours can be a relevant option for pediatric transplant centers to avoid interference with the conditioning regimen and facilitate medical surveillance.